Two-stage removal of giant fibrovascular polyp of the oesophagus. (21st October 2010) - Jose, Paul; Scott, Nigel; Sarela, Abeezar I
Abstract : A patient presented with several months' history of dysphagia, chest pain, symptoms of regurgitation and weight loss. He underwent an upper gastrointestinal endoscopy, which revealed a giant polyp of the oesophagus. After confirming the diagnosis of giant fibrovascular polyp of the oesophagus, the patient underwent a two-stage division of the stalk and retrieval of the polyp. The postoperative period was uneventful and the patient was asymptomatic at the time of discharge. He is being followed up with a plan for surveillance endoscopy in a year.